Treadmill exercise alleviates Alzheimer’s disease pathologies in APP/PS1 mice through modulation of microglial glucose metabolic reprogramming - Liang, Fei; Sun, Feng; Guo, Cuijun; Zhong, Huacong (Frontiers in Aging Neuroscience, 2025)
ObjectiveOur preliminary studies have demonstrated that exercise counteracts Alzheimer’s disease (AD) by mitigating microglia-mediated neuroinflammation and enhancing microglial Aβ clearance. However, the underlying mechanism remains unclear. Given the crucial role of glucose metabolic reprogramming in regulating microglial functions, this study investigated the effects of treadmill exercise on microglial glucose metabolism and associated AD pathologies.Materials and methodsThree-month-old male APP/PS1 transgenic mice were randomly assigned to a sedentary group (AD-SED) or an exercise group (AD-EXE). Age- and sex-matched C57BL/6 mice served as the wild-type control group (WT-SED). The AD-EXE group underwent a 3-month treadmill exercise intervention. Following the intervention, we assessed spatial learning and memory using the Morris water maze test, measured neuroinflammation and Aβ levels via Western blot and ELISA, and analyzed microglial glucose metabolism using LC-MS/MS targeted metabolomics and Seahorse assays.ResultsAPP/PS1 mice exhibited longer escape latencies during place navigation trial and fewer platform crossings during the spatial probe trial; these deficits were partially reversed by treadmill exercise. Furthermore, the exercise intervention significantly reduced hippocampal Aβ levels and suppressed neuroinflammation. Notably, microglia from 6-month-old APP/PS1 mice showed significant impairments in both glycolysis and oxidative phosphorylation (OXPHOS), with a metabolic profile primarily reliant on glycolysis. Treadmill exercise enhanced both glycolysis and OXPHOS, and shifted the metabolic phenotype from glycolytic-dominant toward oxidative phosphorylation, and restored metabolic homeostasis.ConclusionTreadmill exercise promotes microglial glucose metabolic remodeling, which attenuates neuroinflammation and Aβ pathology, and restores spatial learning and memory deficits in APP/PS1 mice.